Federalism and inter-state river water disputes in India - Ranjan, Amit (Researcher on South Asia) (Abingdon, Oxon; New York, USA: Routledge, 2024)
"This book examines the Centre-State and inter-State relations concerning water issues in India. It analyses the federal structure in India and looks at its effectiveness in addressing the inter-state river water disputes in the country through three cases - the Cauvery, Krishna and Mahadayi water disputes. It probes into the physical, political, legal and constitutional measures taken by the Union government and the states to deal with the inter-State and Centre-State tussles over inter-state river waters. The author studies the debate over centralization and decentralization of water resources, as well as the inter-state river water disputes that have aroused feelings of sub-nationalism in disputing regions and states. The possibility of physical infrastructure projects contributing to India's growing water problems are also looked at. This book will be of interest to researchers and students of Environmental Politics, Political Science, Public Policy, Environmental Geography, Indian Politics, South Asian Studies, Environmental Economics, Water Industries, Environmental Policy, River Management, Environment & Resources"--
Indian federalism and water resources -- Cauvery River water dispute -- Krishna River water dispute -- Mahadayi River water dispute -- Managing rivers water: challenges and disputes.
Includes bibliographical references and index.
Keywords: Water resources development -- India; History India; Federalism; Water-supply -- India; River Ecology; Federal government -- India